1983
DOI: 10.1017/s0022112083000750
|View full text |Cite
|
Sign up to set email alerts
|

Stability and heat transfer of rotating cryogens. Part 1. Influence of rotation on the onset of convection in liquid 4 He

Abstract: Equipment is described for performing measurements of the Rayleigh–Bénard instability in a sample of rotating liquid 4He. Data are presented on the dependence of the critical Rayleigh number for the onset of convection on Prandtl number in the range 0·49 < Pr < 0·76 and over a range of dimensionless angular velocities 0 < Ω < 200. Evidence for the existence of subcritical convection is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
4
16
1
Order By: Relevance
“…In two previous reports, Lucas , Pfotenhauer & Donnelly (1983) (Part 1) and Pfotenhauer, Lucas & Donnelly (1984) (Part 2) we have described the stability and heat transfer of standard Benard convection in a rotating system and have demonstrated that the experimental data generally support existing theories. In one major respect, however, the experimental data revealed some unexpected results which we intend to describe in this report in some detail.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In two previous reports, Lucas , Pfotenhauer & Donnelly (1983) (Part 1) and Pfotenhauer, Lucas & Donnelly (1984) (Part 2) we have described the stability and heat transfer of standard Benard convection in a rotating system and have demonstrated that the experimental data generally support existing theories. In one major respect, however, the experimental data revealed some unexpected results which we intend to describe in this report in some detail.…”
Section: Introductionsupporting
confidence: 52%
“…The scatter in Nu in this critical region required in practice that R,/R,, > 1.05 before this distinction could be made. Investigations of this type reveal that the value of 0, for the case when r = 7.81 is less than the value of 200 reported in Lucas et al (1983) and is closer to 52, = 140.…”
Section: Onset Of Convectionmentioning
confidence: 58%
“…31 The rotation about a vertical axis introduces Coriolis force as well as centrifugal force 32 in the flow. Rubio, Lopez & Marques 27 showed interesting effects of the centrifugal force even for small values (∼ 10 −2 ) of the Froude number F r, which is a ratio of the centrifugal force to the force of buoyancy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at high rotation rates the first instability of the conductive state is not to a bulk mode as predicted by Chandrasekhar [1] but rather to a traveling-wave state localized near sidewall boundaries. The first evidence for this mode can be seen in heat transport measurements [2,3]; a partial explanation [4] was based on linear stability calculations [5] which predicted a stationary azimuthally periodic wall mode. Flow visualization of rotating convection in a cylindrical convection cell with radiusto-height ratio ⌫ = 1 revealed, however, that the wall mode was a traveling wave [6,7].…”
Section: Introductionmentioning
confidence: 99%